Association of Flame-Retardant Clothing with Mycosis Fungoides: A Retrospective Analysis - Katherine Park; Vignesh Ramachandran; Jessica Tran; Tejas Joshi; Naveen Garg; Madeleine Duvic (Mattioli1885, 2022)
Introduction: Mycosis fungoides (MF), the most prevalent form of cutaneous T-cell lymphoma (CTCL), has been associated with a variety of environmental and occupational exposures. Flame-retardant clothing (FRC), in contrast to flame-resistant clothing, is chemically treated and may constitute a previously unrecognized occupational hazard. Objectives: To report an association between FRC and MF. Methods: After encountering several young male patients whose onset of MF coincided with the occupational use of FRC and occupation as fire fighters, we did a retrospective search. Additional biopsy proven MF patients with use of FRC were identified by the EPIC electronic medical record using the search terms "CTCL, mycosis fungoides, flame, and flame-retardant." Results: Eight MF patients, all males, ranging in age from 31 years to 64 years (median age, 35 years) with exposure to FRC were identified. MF remission was noted in three patients who discontinued FRC use and in one patient who used a cotton undershirt barrier, while disease persistence was noted in one patient who continued to use FRC. Conclusions: FRC appears to be associated with development of MF through chronic antigen stimulation. Use of FRC is an occupational hazard for fire fighters. Any patient whose MF coincides with use of FRC should avoid further exposure through avoidance or switching to clothing made from inherently flame-resistant fibers.